Nursing Students' Academic Self-Efficacy, Level of Clinical Decision-Making and Attitudes Towards Clinical Practice - Özge Bircan; Buse Ak; Burçin Irmak (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The aim of this study is to examine the relationship between nursing students' academic self-efficacy, clinical decision-making level and attitude towards clinical practice. Method: The data of the descriptive and relationship-seeking study were collected between November 1 and December 31, 2023. The sample of the study consisted of 266 nursing students studying at a public university. The data were collected using the Student Introduction Form, the Academic Self-Efficacy Scale for Undergraduate Nursing Students, the Clinical Decision-Making Scale in Nursing, and the Attitude Scale for Clinical Practices in Nursing Students. Data were analyzed using descriptive statistics, independent t-tests, one-way ANOVA, and Pearson correlation tests. Results: In the study, the average score of the students from the scales was 51.86 (SD: 5.91) on the Academic Self-Efficacy Scale, 93.42 (SD: 13.83) on the Clinical Decision-Making Scale and 96.86 (SD: 12.96) on the Attitude Scale towards Clinical Practices, respectively. There was a weak negative correlation between students' academic self-efficacy and clinical decision-making levels (r=-0.407; p<0.001), and a weak positive correlation between their academic self-efficacy and their attitudes towards clinical practice (r=0.309; p<0.001). A weak negative correlation was found between students' clinical decision-making levels and their attitudes towards clinical practices (r=-0.481; p<0.001). Conclusion: It was found that increasing students' academic self-efficacy increased their positive attitudes towards clinical practice and decreased their clinical decision-making levels. It is recommended to add course contents to ensure the balance between theoretical and practical education in nursing curricula.